Hardware-based efficient Mickey-128 stream cipher with unrolling factors for throughput enhancement - Ananth, Raghavendra; Rao Malode V., Panduranga; Swamy Ramaiah, Narayana (Institute of Advanced Engineering and Science, 2025)
The emerging trend known as